Research on the Cross-Coupling of a Two Axes Gimbal System with Dynamic Unbalance. (18th October 2013) - Abdo, Maher; Vali, Ahmad Reza; Toloei, Alireza; Arvan, Mohammad Reza
The aim of the gimballed stabilization system is to stabilize the sensor's line of sight towards a target by isolating the sensor from the disturbance induced by the operating environment, such as various disturbance torques and body motions. This paper presents a two axes gimbal assembly. The torque relationships are derived considering the angular motion of the base body and the dynamic unbalance. The stabilization loops for the two axes gimbal system are constructed and related to each other with a cross-coupling unit. Next, the overall model is simulated using two approaches and the obtained results are compared to show the correction of the model proposed. Finally, numerous tests are applied to evaluate the model's performance and investigate the effects of torque disturbance considered in this research.